QUALITY AND RELIABILITY CONTROL OF REFURBISHED AUTOMOTIVE PRINTED CIRCUIT BOARDS: EVALUATION CRITERIA, TESTING METHODS, AND IMPACT ON VEHICLE SAFETY - Breusov, Yurii (Public Management and Policy, 2026)
Component-level repair of automotive electronic control units is widely used in practice as an alternative to full replacement. However, there is still no clear, consistent way to judge whether such a repair can be considered reliable. Drawing on 210 real repair cases from 2023–2024, this article looks at how refurbished units are actually evaluated, what signals indicate that a repair will hold over time, and why these decisions have direct safety implications for the vehicle. Methods of analysis and synthesis, a structural-functional approach, and a structured in-depth interview with a practicing specialist were employed. It was found that standard testing with power connection and a diagnostic scanner detects only some of the faults: defects in the interconnections between the board layers remain undetected until the unit is subjected to actual load in the vehicle. Eliminating the root cause of the malfunction in the vehicle prior to unit repair and load testing reduces the rate of repeat failures to 5–10%. The proposed multi-layer validation model combines microscopic inspection, electrical measurements, diagnostic scanning, memory verification, and load, thermal, and mechanical stress testing. The results provide a practical basis for developing a standardized quality-control protocol for independent service centers working with safety-critical automotive electronic modules. For active safety systems, where a failure can directly cause an accident, a latent fault is more dangerous than a complete unit failure: it is not detected by the self-diagnostic system but manifests during emergency braking or a sharp maneuver. The study also demonstrates that repair decisions for safety-critical modules should be based not only on functional recovery but also on the predictability of their behavior under dynamic operating conditions.